Icaritin promotes tumor T‐cell infiltration and induces antitumor immunity in mice. Issue 12 (18th September 2019) - Hao, Haibang; Zhang, Qi; Zhu, Hai; Wen, Yuxiang; Qiu, Ding; Xiong, Jian; Fu, Xiaolan; Wu, Yuzhang; Meng, Kun; Li, Jian
Abstract: Icaritin, a hydrolytic product of icariin isolated from traditional Chinese herbal medicine genus Epimedium, has many pharmacological and biological activities. Here, we show that icaritin can effectively decrease tumor burden of murine B16F10 melanoma and MC38 colorectal tumors in a T‐cell dependent manner. The treatment effects are associated with increased CD8 T‐cell infiltration and increased effector memory T‐cell frequency. In vivo depletion of CD8 T cell using an anti‐CD8 monoclonal antibody abolished the antitumor effect, which supports the critical role of CD8 T cells during icaritin treatment. By analyzing immune cells in the tumor tissue, we found reduced frequency of CD11b + Gr1 + myeloid‐derived suppression cells (MDSCs) infiltration and downregulation of PD‐L1 expression on MDSCs after icaritin treatment. This was not limited to MDSCs, as icaritin also decreased the expression of PD‐L1 on neutrophils. Importantly, the combination of anti‐PD‐1/CTLA‐4 and icaritin significantly enhances antitumor ability and increases the efficacy of either treatment alone. Our findings reveal that icaritin induces antitumor immunity in a CD8 T‐cell‐dependent way and justify further investigation of combining immune checkpoint therapy to icaritin‐based antitumor therapy. Abstract : Here, we revealed that icaritin treatment enhances T‐cell‐mediated antitumor immunity in a murine B16F10 melanoma model. The treatment effects are associated with increased CD8 T‐cells accumulation in tumors. Icaritin also reduces the frequency of MDSCs in tumors and the expression of PD‐L1 on MDSCs.